Path analysis of physical attributes in maize (Zea mays L.) under conventional cultivation system (Research, Society and Development, 2021)
The cultivation of maize (Zea mays L.) has extreme economic and social importance, as it is cultivated in practically all parts of the planet. The objective of this work was to evaluate the physical attributes that best describe the mass of the corn ears. The experiment was conducted in the facilities of the experimental area of the technological center of family farming (CETAF), located in the southeast region of Pára, in the municipality of Parauapebas. Path analysis was performed using the GENES software, responsible for detailing the relationship between one variable and another. Directly, that the attributes total mass of the ear and mass of grains of the ear, were the attributes that best represent the mass of the ear. Indirectly, we observed that the total mass of the ear significantly influences the mass of the ear grains.